Aggregation dynamics of nanoparticles at solid–liquid interfaces. Issue 28 (7th July 2017) - Tian, Xuezeng; Zheng, Haimei; Mirsaidov, Utkur
Abstract : The dynamics of molecules or nanoparticles (NPs) at solid–liquid interfaces plays an important role in many natural and industrial processes. Abstract : The dynamics of molecules or nanoparticles (NPs) at solid–liquid interfaces plays an important role in many natural and industrial processes. However, the effects of a solid–liquid interface on NP motion and on the interactions between these NPs is still not well understood. Here, using in situ liquid cell transmission electron microscopy (TEM), we directly observed the movement of gold NPs and their aggregation dynamics at solid–liquid interfaces. We found that the solid surfaces transiently pin the NPs during their aggregation, dampening their translational and rotational movements. This surface pinning reduces both the movement of NPs and their aggregation rate as the aggregates grow by attachment. However, the pinning of the NP aggregates affects their translational and rotational motions differently. Initially, with increasing aggregate size, the aggregate's translational motion dampens more than its rotational motion. Consequently, the initial aggregation stages are driven by both the translational and rotational motions, whereas the rotational motion dominates the later aggregation stages. Our results provide insight into the movements of NPs and their aggregates at solid–liquid interfaces, which may assist in the future design and control of NP assemblies at interfaces.